Pengaruh Lingkungan Kerja Fisik dan Motivasi Kerja terhadap Kinerja Karyawan pada Bagian Cutting di CV. XYZ - Salwa Ghaissani Dwi Putri; Aam Rachmat Mulyana (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to determine the effect of the physical work environment and work motivation on employee performance in the cutting department at CV. XYZ. The research method used was quantitative with a descriptive and associative approach. Data were collected through observation, documentation, and questionnaires from 51 respondents. Data were analyzed using multiple linear regression with SPSS version 26. The results showed that the physical work environment and work motivation, both partially and simultaneously, had a positive and significant effect on employee performance, with regression coefficients of 0.330 and 0.279, respectively, and a coefficient of determination of 82.5%. The conclusion of this study is that improving the quality of a comfortable and conducive physical work environment and providing good work motivation can optimally improve employee performance in the cutting department at CV. XYZ.   Keywords: Work Environment, Work Motivation, Employee Performance, Company Performance